Exercise Effects on Cognition in Older African Americans: A Pilot Randomized Trial - Gwizdala, Kathryn L.; Brouillete, Robert; Beyl, Robbie; Johnson, William; Hebert, Callie; Carter, Leah; Harris, Melissa; Newton, Robert L.; Carmichael, Owen T. (Frontiers in Aging Neuroscience, 2022)
INTRODUCTION: Regular physical activity lowers risk for cognitive decline and neurodegenerative disorders. Older African Americans (AAs) have been underrepresented in trials that increased physical activity to improve cognitive outcomes. METHODS: 56 sedentary, older, cognitively healthy AAs (avg. 69.2 ± 3.4 yrs. old) were randomized in 1:1 ratio into either a 12-week successful aging group (SAG) or a 12-week physical activity group (PAG). Participants in SAG attended weekly 60-minute educational sessions in which healthy aging topics were discussed. Participants in PAG attended supervised physical activity sessions twice per week at local YMCAs (90-120 min/week) and were prescribed 2-3 days per week of home-based activity. The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) assessed cognitive function. ANCOVA models compared mean 12-week change in global cognition and subdomain scores between groups with secondary analyses for sex differences. Effect sizes for RBANS were calculated. RESULTS: The RBANS global cognition score (SAG Est. 5.6 ± 1.8, effect size = 0.37, p = 0.003) and several subdomain scores (one-sample T tests, all p <0.05) increased significantly within the SAG. Scores for global cognition increased more in SAG than in PAG (Change Estimate, PAG minus SAG: -4.6 ± 2.5 points, effect size = 0.31) at a trend level (p = 0.072). SAG females increased their global cognition score more than PAG females and more than males in either PAG or SAG (all p <0.035). DISCUSSION: A 12-week physical activity intervention did not improve cognitive functioning among older AAs but a comparator healthy aging education program did. Inadequate physical activity dosage or duration, SAG members acting on health-related information from educational sessions, and/or social stimulation within the SAG may have contributed to these results. Future studies should combine socially engaging activities with vigorous physical activity for cognitive enhancement among cognitively healthy older African Americans.